Regenerative Medicine Modalities for the Treatment of Degenerative Disk Disease. Issue 10 (December 2021) - McDonnell, Jake M.; Ahern, Daniel P.; Ross, Tayler D.; Morrissey, Patrick B.; Wagner, Scott C.; Vaccaro, Alexander R.; Butler, Joseph S.
Abstract : Degenerative disk disease is a pathologic state associated with axial skeletal pain, radiculopathy, and myelopathy, and will inevitably increase in prevalence in parallel with an aging population. The objective of regenerative medicine is to convert the inflammatory, catabolic microenvironment of degenerative disease into an anti-inflammatory, anabolic environment. This comprehensive review discusses and outlines both in vitro and in vivo efficacy of regenerative treatment modalities for degenerative disk disease, such as; mesenchymal stem cells, gene therapy, tissue engineering, and biologic treatments. To date, clinical applications have been limited secondary to a lack of standardized high quality clinical data. Additional research should focus on determining the optimal cellular makeup and concentration for each of these interventions. Nevertheless, modern medicine provides a new avenue of confronting disease, with methods surpassing traditional methods of removing the pathology in question, as regenerative medicine provides the opportunity to recover from the diseased state.